On the concept of “Comprehensiveness” in Information Services: The case of the online translation aid and hosting service Minna no Hon'yaku / Kyo Kageura and Takeshi Abekawa - Kageura, Kyo; Abekawa, Takeshi (2011)
The aim of this research is to clarify the concept of ―comprehensiveness‖ and its relationship to the concept of ―normativeness‖ in language reference tools and information for online translators, from the point of view of strategically providing useful reference information via a translation aid-service. The concept of ―comprehensiveness‖ in reference information has not been explored fully to dateThe questions to be answered are: What are the factors that determine different levels of ―comprehensiveness‖ and ―normativeness‖? How can ―comprehensiveness‖ be classified in relation to different types of reference lookup, and what kind of strategies can we define and adopt in developing and providing useful reference resources automatically or semi-automatically? While it is widely held that careful user studies are important in the strategic design of information services, empirical studies of potential users are not sufficient in the conceptualisation and development of advanced information services and tools which incorporate innovative functions or features, because quite frequently users do not understand what they want from the new information technologies. This is all the more true for issues in which one or more of the key concepts are not understood clearly. The question we wished to address fall precisely within this category, as the concept of ―comprehensiveness‖ has not yet been explored fully. We therefore took a deductive and analytical approach, firstly listing up the factors that affect the concept of ―comprehensiveness‖ and related concepts, with special reference to the translation-aid site Minna no Hon'yaku (translation of/by/for all: http://trans-aid.jp/), and deriving the classification of and desiderata for language reference tools and information from the objective of helping online translators. Although we adopted an analytical and deductive approach, the whole argument is implicitly supported by our own experience with actual translators' behaviour on the site Minna no Hon'yaku. Results of the analysis revealed that, within a framework of providing language reference tools for translators in general and in the context of the online translation-aid environment in particular, three different types of combinations of ―comprehensiveness‖ and ―normativeness‖ are of prominence and importance, namely: (i) task-oriented normativeness/comprehensiveness; (ii) domain-oriented normativeness/comprehensiveness; and (iii) user-oriented normativeness/comprehensiveness